Sarah Grimké as Biblical Commentator - Pope-Levison, Priscilla (Harvard theological review, 2025)
Mark Noll recognized that "the most comprehensive defense of female activity in public life came from Sarah Grimké." Claudia Setzer lauded Grimké’s Letters, as "the first sustained analysis of women’s rights stemming from biblical and theological argument to be written by an American." Scholars have studied her use of the Bible, including her critique of translations, but none has detailed Grimké’s use of the influential whole-volume commentaries of Matthew Henry, Thomas Scott, and Adam Clarke. This article documents her citations, critiques, and editing of those commentaries through selection, interruption, omission, and paraphrase. It focuses upon her thirteenth and fourteenth letters, in which Grimké interpreted Acts 2:1-4, 1 Cor 11:4-5 and 14:34-35, and 1 Tim 2:8-12. By studying her critical engagement with commentaries, we demonstrate the veracity of Grimké’s contention that women "shall produce some various readings of the Bible a little different from those we now have."